(untitled) (Research, Society and Development, 2022)
This paper aims to analyze the characteristics of self-compacting mortar (SCM) with the partial replacement of cement by water treatment sludge (WTS). This replacement aims to contribute to minimize environmental degradation arising from the production of materials used in construction and to give a sustainable destination to the sludge generated in water treatment plants. In this study, the substitution of cement in 10 and 20% for the WTS from the Itajubá Water Treatment Plant in Minas Gerais was analyzed. The residue was collected, filtered, dried and ground, so that the granulometric analyses could be performed and the data inserted in the EMMA particle packing software. Regarding the mortar, the properties in the fresh state were verified through the spreading and flow tests, in which all mixtures could be defined as self-compacting. Regarding the mechanical properties, compression, flexural tensile and modulus of elasticity tests were performed after 28 days of curing. In the mixtures containing WTS, the mechanical strengths and modulus of elasticity decreased. Furthermore, in the hardened state, a reduction in specific mass and an increase in the voids index and absorption was observed in the traces containing WTS. The results indicate that WTS could be used only for non-structural function. However, the results obtained reinforce the need for further studies on the subject, maintaining the possibility of using the WTS in civil construction.